Comparative Studies on Quality Changes of Air Blast and Plate Frozen Mackerel (Rastrelliger kanagurta) During Frozen Storage - T.K., Srinivasa Gopal; I.P., Lakshmisha; C.N., Ravishankar; Ninan, George (Fishery Technology, 2025)
Mackerel (Rastrelliger kanagurta Cuvier ) frozen in commercial plate and air blast freezers were studied to compare the quality changes during frozen storage (-180C)/ The frozen fish were sealed in polythene bags of food grade Linear Low Density Polyethylene (LLDPE), 120 gauge thick conforming to IS: 9845 - 1981) then packed in 5-ply corrugated fiberboard carton and were analyzed for changes in quality during storage at -180C. The moisture and protein content in air blast frozen samples were decreased (p0.05) in PV of both the samples. TBA of air blast frozen samples showed an increasing trend (p0.05). The TMA-N and TVB-N of both the samples showed an increasing trend but air blast frozen samples showed little higher values (p